2012
DOI: 10.1177/1080569912459752
|View full text |Cite
|
Sign up to set email alerts
|

Toward Learner-Centered Teaching

Abstract: Through the past several years, the emphasis in education has shifted from a teachercentered to a learner-centered approach. Traditional teaching has too often been based on a passive lecture model, dependent on an expert teacher who funnels knowledge into the somewhat retentive minds of students. More current learning theory suggests a different role for teachers-that of facilitators. Based on research about how people learn, this article advocates that teachers use more active, inductive instruction in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 6 publications
0
49
0
Order By: Relevance
“…29 Most participants described difficulties engaging students in lecture. One participant described how they tried to use more active learning strategies, only to be met with student resistance.…”
Section: Experience Of Previous Teaching Methodsmentioning
confidence: 99%
“…29 Most participants described difficulties engaging students in lecture. One participant described how they tried to use more active learning strategies, only to be met with student resistance.…”
Section: Experience Of Previous Teaching Methodsmentioning
confidence: 99%
“…Smart, Witt, & Scott, 2012) and have offered few opportunities for students to engage in meaningful conversations (Lefstein & Snell, 2011 If teachers of ELLs continue to focus on low-level skills such as vocabulary and grammatical structures (Fillmore & Fillmore, 2012;Hakuta & Santos, 2012) and on fact-based-questions, with little effort to elicit elaboration from them (Zwiers, 2007), ELLs will ultimately be underprepared for 21 st Century global participation, and the opportunity gap for ELLs will persist. To address this problem of practice, this study was led by the research question: What is the experience of high school content teachers who are implementing the Common Core State…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that most teaching in U.S. high schools is teacher-centered, where teachers impart their expertise upon students, and students receive the content as receptacles (e.g. Smart, Witt, & Scott, 2012). This carry-over from the factory-model of education is problematic in preparing students, especially ELLs, to be ready as 21 st Century graduates.…”
Section: Common Core State Standards (Ccss) For English Language Artsmentioning
confidence: 99%
See 2 more Smart Citations